ARMY WIVES SERVE, TOO (A NOVELISTIC SENSE IN SOCIOLOGICAL IMAGINATION) - wida ayu (Brawijaya Journal of Social Science, 2018)
We frequently hear about the heroic soldiers struggle for their nation, but we seldomly hear about what their wives have made. Army wives are conjoined by unwritten codes. They are expected to endure hardships with kindness and tragedies with heads held high (Moelker, Andres, and Poot 2006). The media commonly focuses only on the familiesâ€™ tearful goodbyes and tearful reunions â€“ or, in the case of spouse murders, their deaths. Yet the reality is far more complex and breath-taking.Â